A rapid assessment of health system preparedness and response to the COVID-19 pandemic in Guinea - Alexandre Delamou; Abdoulaye Sow; Thierno O. Fofana; Sidikiba Sidibé; Karifa Kourouma; Maurice Sandouno; Abdoulaye Touré; Thierno M. Tounkara; Fréderic Le Marcis; Wim van Damme (AOSIS, 2022)
Epidemic-prone diseases have high adverse impacts and pose important threats to global health security. This study aimed to assess levels of health facility preparedness and response to the COVID-19 pandemic in Guinea. This was a cross-sectional study in public and private health facilities/services across 13 Guinean health districts. Managers and healthcare workers (HCWs) from departments in each facility/service were interviewed. Descriptive statistics and comparisons were presented using Pearson's Chi-Squared Test or Fischer exact test. Totally, 197 managers and 1020 HCWs participated in the study. Guidance documents and dedicated spaces for management/isolation of suspected COVID-19 cases were available only in 29% and 26% of facilities, respectively. Capacities to collect (9%) and safely transport (14%) samples were low. Intensive care units (5%), dedicated patient beds (3%), oxygenators (2%), and respirators (0.6%) were almost lacking. While 36% of facilities/services had received infection prevention and control supplies, only 20% had supplies sufficient for 30 days. Moreover, only 9% of HCWs had received formal training on COVID-19. The main sources of information for HCWs were the media (90%) and the internet (58%). Only 30% of HCWs had received personal protective equipment, more in the public sector (p0.001) and in Conakry (p=0.022). This study showed low levels of preparedness of health facilities/services in Guinea and highlighted a lack of confidence among HCWs who felt unsafe at their workplace. Better governance to improve and maintain the capacity of the Guinean health system to respond to current and future epidemics is needed.